2018
DOI: 10.1177/1747493018801222
|View full text |Cite
|
Sign up to set email alerts
|

Breaking up sitting time after stroke (BUST-stroke)

Abstract: Frequent, short bouts of light-intensity physical activity did not have a significant effect on post-prandial plasma glucose and insulin in this sample of people with stroke. Further studies are needed to identify strategies that improve inactivity-related glucose metabolism after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
0
18
1
3
Order By: Relevance
“…A total of 29 trials (33 articles) were identified in our search as meeting all inclusion criteria (Fig 1). One (two articles [20, 30]) additional trial was included on the 13 th June 2018. Therefore, a total of 30 trials (35 articles) were included in this review, of which 53% were not registered with a trial registry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 29 trials (33 articles) were identified in our search as meeting all inclusion criteria (Fig 1). One (two articles [20, 30]) additional trial was included on the 13 th June 2018. Therefore, a total of 30 trials (35 articles) were included in this review, of which 53% were not registered with a trial registry.…”
Section: Resultsmentioning
confidence: 99%
“…All trials used a randomised crossover design, expect for one which used a balanced crossover design [31]. In 20 trials, interventions occurred in a laboratory or research facility where participants were supervised during each condition [12, 14, 16, 18, 20, 30, 3250]. One trial was completed under supervised conditions in an office setting [51] and nine trials were conducted in a laboratory or research facility [19, 31, 5258] where participants where not reported to be observed during conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce dietary-induced variations in glucose and insulin, dietary intake will be standardised 24 h prior to, and during, each experimental condition based on the procedures employed in our previous trial [ 9 , 10 ]. Participants will follow a dietitian prescribed meal plan and be provided with a standardised pre-experimental day evening meal and asked to abstain from alcohol, caffeine and moderate-to-vigorous physical activity for 48 h before the experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…While demonstrating proof of concept, the schedule of activity breaks (3 min every 30 min) is not clinically applicable in every-day life. Therefore, this new study builds on our previous BUST-Stroke trial [ 9 , 10 ] and aims to investigate the dose-response of STAND-EX bouts to reduce recurrent stroke risk and improve cardiometabolic health in stroke survivors.…”
Section: Introduction and Rationalementioning
confidence: 99%